Identification of Dominant Factors Causing Barge and Tug Shipping Accidents By Analyzing Secondary Data on Accidents on The Mahakam River and Palembang - Dony Ari Nugroho (Green Publisher Indonesia, 2025)
Barge and tugboat shipping accidents in the Mahakam River and Palembang continue to occur from year to year, causing material losses, fatalities, and disruptions to transportation and economic activities. This problem indicates the existence of dominant factors that need to be thoroughly identified, whether from the aspects of ship technical conditions, human negligence, environmental conditions, or weaknesses in regulation and supervision. This study aims to identify the dominant factors causing accidents through secondary data analysis, which can serve as the basis for recommendations to improve maritime safety. This research employs a descriptive qualitative method with documentation techniques to collect secondary data related to barge and tugboat accidents. Data analysis was carried out using the Miles and Huberman model through three stages: data reduction, data presentation, and conclusion drawing with verification. The results of the study indicate that accidents are influenced by three main groups of factors, namely human factors (operator negligence, lack of training, and low safety awareness), technical factors (unseaworthy vessels, engine damage, infrastructure limitations), and natural factors (extreme weather, strong currents, inadequate water depth). The implications of this research underscore the need for integrated measures, including enhancing crew competence, improving shipping infrastructure, implementing early warning systems, and strengthening regulations and oversight. The implementation of these recommendations is expected to reduce accident rates and support the sustainability of river transportation in both regions.